1975
DOI: 10.1037/h0076209
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of mouse killing and apomorphine-induced social aggression in rats by local anesthesia of the mystacial vibrissae.

Abstract: Local anesthesia of the facial epidermis can effect a substantial decrease in shock-elicited fighting of paired rats. The present experiments constitute methodological extensions to mouse killing and spontaneous drug-induced social aggression. In the first experiment, known mouse-killing rats were given bilateral lidocaine or placebo injections administered under ether anesthesia. Attack and kill latencies were significantly longer under lidocaine than under placebo; all subjects killed under placebo, whereas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
1

Year Published

1976
1976
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 17 publications
3
16
1
Order By: Relevance
“…Thus, the effect of nonspecific dopamine agonists on aggressive behavior may be in part determined by not only the dose of the drug but also the specific behavioral history of the individual. These conditions can also interact such that high doses of amphetamine, or amphetamine combined with altered levels of arousal such as during opiate withdrawal, can lead to heightened aggressive behavior (Hasselager et al 1972;Geyer and Segal 1974;Puech et al 1974;Thor and Ghiselli 1975;Baggio and Ferrari 1980). Decreases in rodent aggressive behavior following selective destruction of cathecholaminergic neurons or inhibition of tyrosine hydroxylase have also been reported, but this effect on aggression appears to be due more to a reduction in norepinephrine than to any reduction in dopamine (Eichelman et al 1972;Ellison 1976;Matsumoto et al 1995;Serova and Naumenko 1996).…”
Section: Pharmacological Manipulations Of Dopaminergic Systemsmentioning
confidence: 92%
“…Thus, the effect of nonspecific dopamine agonists on aggressive behavior may be in part determined by not only the dose of the drug but also the specific behavioral history of the individual. These conditions can also interact such that high doses of amphetamine, or amphetamine combined with altered levels of arousal such as during opiate withdrawal, can lead to heightened aggressive behavior (Hasselager et al 1972;Geyer and Segal 1974;Puech et al 1974;Thor and Ghiselli 1975;Baggio and Ferrari 1980). Decreases in rodent aggressive behavior following selective destruction of cathecholaminergic neurons or inhibition of tyrosine hydroxylase have also been reported, but this effect on aggression appears to be due more to a reduction in norepinephrine than to any reduction in dopamine (Eichelman et al 1972;Ellison 1976;Matsumoto et al 1995;Serova and Naumenko 1996).…”
Section: Pharmacological Manipulations Of Dopaminergic Systemsmentioning
confidence: 92%
“…In rats whisker are required in attacks on mice (Thor and Ghiselli, 1975), play a significant role in controlling maternal aggression (Kolunie and Stern, 1990) and both in aggressive and non-aggressive social behaviors (Thor, 1976; Blanchard et al, 1977; Sarna et al, 2000; Brecht and Freiwald, 2011; Wolfe et al, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…For example, a study by Thor and Ghiselli (1975) reported high levels of aggression in animals injected intraperitoneally with a 20-mg/kg dose of apomorphine. In our study, a l5-mg/kg dose of apomorphine yielded aggressive behavior no different from control.…”
Section: Discussionmentioning
confidence: 99%
“…These arbitrary procedures, especially the selective use of "high fighters," may have increased the probability of fmding a drug-induced reduction in aggression, in view of known rate-dependency phenomena. Finally, the data available on dose-response relationship are unclear, with a wide range of doses and routes of administration being used by different investigators (McKenzie, 1971;Senault, 1970;Thor & Ghiselli, 1975).…”
mentioning
confidence: 99%